Analysis of Influenced Factors on Consumer Behaviour: The Demand of Chicken Egg’s in TebingTinggi City - S H Putri; A H Daulay; Hamdan; E Mirwandhono; T H Wahyuni (Jurnal Peternakan Integratif, 2018)
The purpose of this study were to identify factors that affect the demand for chicken eggs and to find out the correlation of factors that affect consumer behavior in purchasing chicken eggs in Tebing Tinggi City. The research used primary data obtained from questionnaires or interviews. The research method was multiple linear regression methods, spearman rank correlation and contingency correlation. The results showed that the price of chicken eggs and the income had real effect to the demand for chicken eggs in the area of research. The result of spearman rank correlation and the contingency correlation showed that there was a real correlation between the income with a consumer behavior in purchasing chicken eggs, while the age, employment, and number of consumer dependents, did not show real correlation with consumer behavior in purchasing chicken eggs.